(untitled) (Journal of Intellectual Property Rights (JIPR), 2023)
Indian Copyright Act, 1957 provides a private right in copyright which extensively deals with provisions that guarantee access to knowledge as well. Copyright is an exclusive and assignable legal right given to the author for a particular period for original literary, dramatic, artistic works, and musical work whether published or unpublished. These rights are not absolute but subject to restrictions and limitations imposed by law. Section 52 of the Copyright Act, 1957 is one such provision that restraints the exclusive enjoyment of rights given to the copyright holder. As per Section 52 (1)(o) of the Copyright Act, 1957 a non-commercial library is permitted/allowed to make three copies of a book for library use, provided such books are not available for sale in India. The present article is about the concept of fair dealing which is originated from the Common of laws of England. Although, the concept of fair use and fair dealing are used synonymously, the Indian Copyright Act, 1957 deals with fair dealing under Section 52 of the Copyright Act, 1957. The reproductions of works for research or private study, taking photocopy for research and educational purpose, etc., are covered under the doctrine of fair use. This paper will explain the conceptual framework of the Indian Copyright Act and the empirical reality in libraries of Maharashtra. It attempts to empirically test the usage of fair use provisions under the Indian Copyright Act and the awareness among librarians of Colleges and Universities in Maharashtra. The research methodology used for the present study is both doctrinal and non-doctrinal. It was observed that most of the librarians are aware of Copyright Law and copyright exceptions but when it comes to the implementation librarians also face difficulty and it leads to the infringement of copyright.